2010
DOI: 10.1111/j.1740-0929.2010.00811.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of muscular glutamate metabolism by high‐protein diet in broiler chicks

Abstract: The major taste active component, glutamate (Glu), improves the taste of meat. In this study, we investigated the effect of a short-term high-protein (HCP) diet on the intramuscular free Glu content to improve the taste of meat. Furthermore, we elucidated how the muscle free Glu content was controlled by the HCP diet. Chicks (14 days old) were fed the control diet or HCP diet for 10 days. Plasma and muscle free amino acid concentrations, and activity and messenger RNA (mRNA) expression of muscle enzymes relate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…These diets contained 100% and 150% of Lys recommended by the National Research Council (NRC 1994). This additional level of 150% Lys was similar to that of high CP diet used in our previous studies (Kobayashi et al 2011). This additional level of 150% Lys was similar to that of high CP diet used in our previous studies (Kobayashi et al 2011).…”
Section: Experimental Dietssupporting
confidence: 83%
See 1 more Smart Citation
“…These diets contained 100% and 150% of Lys recommended by the National Research Council (NRC 1994). This additional level of 150% Lys was similar to that of high CP diet used in our previous studies (Kobayashi et al 2011). This additional level of 150% Lys was similar to that of high CP diet used in our previous studies (Kobayashi et al 2011).…”
Section: Experimental Dietssupporting
confidence: 83%
“…The importance of intracellular lysine (Lys) metabolism in the regulation of free Glu content in muscle has been demonstrated by Kobayashi et al (2011). The saccharopine pathway is the major Lys degradation pathway in mammals and birds (Higashino et al 1967;Hutzler & Dancis 1968;Grove & Roghair 1971;Wang & Nesheim 1972).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the current study determined the crude fat content of breast muscle. Recently, Kobayashi et al (2011) reported that 10 days of a high CP diet could increase the free Glu content of the breast muscle of broiler chickens. Thus, the difference in the SFV could not be explained by differences in the crude fat content.…”
Section: Discussionmentioning
confidence: 99%
“…Glu is a major active taste component in meat (Kato & Nishimura 1987;Fujimura et al 1996). Recently, we successfully modified the free Glu content of muscle using a nutritional approach, where high dietary CP increased the free Glu content in the muscles of chickens (Kobayashi et al 2011). The addition of Glu to the solution enhanced the sweetness, saltiness and umami taste compared with the reference solution.…”
Section: Introductionmentioning
confidence: 99%
“…; Kobayashi et al . ). In addition, our recent study showed that short‐term feeding of a high Lys diet also increased the concentrations of free Glu in muscle (Watanabe et al .…”
Section: Introductionmentioning
confidence: 97%